IMPLEMENTASI KEBIJAKAN TUNJANGAN PROFESI GURU SD DAN SMP DI KOTA TANGERANG SELATAN - Sulistia, Wulan Sulistia Anjany; Abdul Rahman (stiatabalong.ac.id, 2024)
Education is an important aspect in national development programs. One pf the reasons why education in Indonesia is still low is the low quality of teachers. The government is trying to improve teacher quality by improving teacher welfare in an effort to combat the low quality of education. One of them is by providing Teacher Professional Allowances for teachers who have teaching certificates. This study focuses on the Implementation of the Professional Allowance Policy for Elementary and Middle School Teachers in South Tangerang City. The aim of this research is to determine and analyze the implementation of the Elementary and Middle School Teacher Professional Allowance Policy and identify the factors that influence the policy implementation process in South Tangerang City. This research method uses a descriptive method with a qualitative approach. The data analysis technique used is data reduction, data presentation and also drawing conclusions. Data collection techniques through triangulation, namely interviews, observation and documentation. Determining 15 informants using purposive sampling technique. The research results obtained are that the implementation of the Professional Allowance Policy for Elementary and Middle School Teachers in South Tangerang City which was studied using 4 indicators according to Edward III has gone well even though it is not completely optimal. There are still obstacle factors such as incomplete socialization in the communication aspect, lack of science and technology for teachers in the resource aspect, delays in disbursing the Teacher Professional Allowance schedule in implementing policies. Keywords : Policy Implementation, Teacher Professional Allowance, Education authorities, Certification, Teacher.